SARS-CoV-2 exposure, symptoms and seroprevalence in healthcare workers in Sweden - Ann-Sofie Rudberg (Nature Portfolio, 2020)
Healthcare workers may be at higher risk of SARS-CoV-2 infection than the general population. Here, the authors report 19% seroprevalence of SARS-CoV-2 antibodies among 2,149 employees in a Swedish hospital. Seroprevalence was associated with patient contact and higher than the seroprevalence in the community in same time period.